Late Holocene uplift of a coastal terrace near the Akatore Fault, southern New Zealand. Issue 4 (2nd October 2021) - Craw, Dave; Parvizi, Elahe; Read, Stephen; Fraser, Ceridwen I.; Waters, Jonathan M.
ABSTRACT: Late Holocene earthquake activity on the reverse Akatore Fault of southeastern South Island has caused uplift along >20 km of nearby coastline, with the last major earthquake event c. 800 years ago. Fault-related uplift has exposed a prominent rocky and sandy terrace along the coastline. We used a combination of approaches including land-based observations, LIDAR remote sensing, and radiocarbon dating of shell deposits, to reveal the extent and nature of past uplift in the region. Cumulative uplift of this terrace varies laterally from <1 m at the northern and southern ends to possibly exceed 5 m in the central portion. The coastal terrace lies below a steep fossil sea cliff. Caves at the base of this cliff contain shells with radiocarbon ages <500 years old, implying persistence of large wave incursion right across the terrace after uplift. A major uplift event of ∼2 m along the whole 20 km of shoreline caused extirpation of some intertidal kelps that now have genetically distinct lineages in the uplift zone.